Effect of iron (Fe3+) doped calcium copper titanate oxide (CCTO) - Sabastanus, Kait (2016)
The CaCu3Ti4-xFex012 (x = 0, 0.05 and 0.1) ceramics were synthesized by solid state reaction route and the microstructure and dielectric properties were studied. The XRay Diffraction (XRD) was used to analysis the lattice parameter and it was found that as the dopant contents increase the lattice parameter decrease. The microstructures were analyzed using Field Emission Scanning Electron Microscopy (FESEM) and it shows that as the dopant content increase the grain size increase. The dielectric measurement were performed at room temperature shows that with pure Calcium Copper Titanate (CCTO) doped with iron (Fe3+), the dielectric permittivity (ε) at frequency 10 Hz decreases. Same goes with dielectric loss (tanδ), decrease when pure CCTO doped with iron (Fe3+).